Three Sixty Coffee / Nor Syahdani Zulkifli ... [et al.] - Zulkifli, Nor Syahdani; Zulkiflee, Nurin Aina Nabihah; Zulkarnain, Nur Ayuni Kartini; Mohd Sufian, Nur Hadirah Sofia; Kader, Muhammad Aiman Muzamil; Tengku Baharim, Tengku Aishah Fatimah (2021)
Three Sixty Coffee business is mainly based on coffee culture flourishing throughout every corner of the world. We are offering various kind of coffee that come from three (3) different continent which is Middle Eastern, African and East Asian to let our customer enjoying and experiencing different flavour that undeniably will give them a full satisfaction. The name of our business is Three Sixty Coffee. The name was suggested from one of our very one partner with the followed statement quoting “Scent of Coffee Lovers ” as to differentiate our uniqueness since seeing that there are so many coffee shops available in Selangor. Three Sixty Coffee business is located in Setia City Mall Convention Centre, Setia Alam Selangor. The business will operate in a shop lot that is leased to us by the Setia City Mall Management. The management (Setia City Mall) also gave us (The business) a very strategic place of operation which is nearby to a popular coffee shop such as Starbuck and next to the Sushi King shop and nearby other restaurant that attracts many customers and will directly help us to attract customers to try our tasty coffee beans. The total project implementation of our business is an average of amount which every partner of six (6) in the business will invest to start this business. With that amount of money, we are managed to allocate a supplier from each continent which is Saudi Arabia, Morocco and Japan. The supplier will supply Three Sixty Coffee the authentic coffee beans per month to preserve and sustain the authenticity. Three Sixty Coffee will aim to give the highest of satisfaction to coffee lovers with decent ambiance. Furthermore, we try to give soothing and unique environment inside the coffee shop. With the above statements, our business is very keen on operating on the highest level and we hope to offer our customers with the very finest quality of coffees that they deserve. With that, in order to attract such high interest from the public, our business offers the highest quality with an exceptionally affordable prices for the customers and coffee lover members via membership cards.